PEMBATALAN PERJANJIAN SEWA MENYEWA TANAH DAN RUKO TANPA JANGKA WAKTU KAITANNYA DENGAN PENJUALAN OBJEK SEWA MENYEWA OLEH PEMILIK (Studi Kasus Putusan Nomor 362/Pdt.G/2013/PN.Mdn) - Ujung, Lolonta Gabriella Exaudita; Purba, Hasim; Siregar, Mahmul (Universitas Wiralodra, 2024)
Land lease agreements and shophouses without a term in Indonesia often cause complex legal problems, especially when the lease object is sold by the owner. This study analyses the case in Decision Number 362/Pdt.G/2013/PN Mdn, which highlights the conflict between the new owner and the tenant in an indefinite lease situation. Using normative juridical research methods with a descriptive approach and qualitative analysis, this study explores the validity and legal protection of indefinite lease agreements, as well as the application of the law by the panel of judges in the case. The results of the study show that although the Civil Code justifies indefinite lease agreements, this practice has the potential to create legal uncertainty. The principle of